Susceptibilidad de la rata Sigmodon hispidus (Rodentia: Cricetidae) al Toxoplasma gondii (Eucoccidia: Sarcocystidae) - Chinchilla C, Misael (1996)
Sigmodon hispidus, a eotton rat, was inoeulated with taehyzoites or ooeysts of Costa Rican strains of Toxoplasma gondii to demonstrate the resistanee to this parasite,a s eompared with miee,h amster and white rat infeetion. Suseeptibility to taehyzoite inoeulation was higher in this animal than in white rats but lower than in the other animals. ¡ndependent to the Toxoplasma strain studied, ooeyst infeetion was less lethal for S. hispidus when eompared with miee and hamsters; the results were similar to ¡hose observed for white rats. There is a probable participation of this wild animal in the natural Toxoplasma life eycle.